POST-HARVEST SOIL TEST VALUES (PHSTVS) PREDICTION EQUATION FOR A PEARL MILLET BASED CROPPING SEQUENCE ON AN INCEPTISOL - UDAYAKUMAR SEKARAN; R. SANTHI; P. DEY; S. MEENA; S. MARAGATHAM (The Bioscan, 2019)
Analyzing soil samples for prescribing soil test based fertilizer doses after each crop in a sequence is time, labour and energy consuming and involves additional cost. With a view to develop post-harvest soil-test values (PHSTVs) prediction equations with multiple linear regression, field experiments were conducted during 2015-16 by adopting Inductive cum Targeted yield model, on an Inceptisol (Vertic Ustropept) with pearl millet under integrated plant nutrition system (IPNS). The experiment was laid out in a fractional factorial design comprising twenty-four treatments. When grain yield was considered, the predictability values of KMnO4-N, Olsen-P, and NH4OAc-K under NPK plus FYM @ 12.5 t ha-1 treatment were 98.4, 97.5, and 98.1%, respectively. When uptake was considered, the predictability values of KMnO4-N, Olsen-P, and NH4OAc-K under NPK plus FYM @ 12.5 t ha-1 treatment were 98.4, 97.6, and 98.1%, respectively. Significant R2-values (>0.65) were recorded for these regression equations which could be used with confidence for the prediction of post-harvest KMnO4- N, Olsen-P and NH4OAc-K. The data on observed and predicted soil test values of available N, P and K were in good agreement with each other, proving the validity of the post-harvest soil test values prediction equations as evidenced by highly significant correlation.